Pengaruh Pemberian Bahan Organik Pada Lubang Resapan Biopori Modifikasi Terhadap Kontribusi Ketersediaan Unsur Hara Bagi Tanaman Kelapa Sawit - Yudhi Ahmad Nazari; Fakhrur Razie; Noor Aidawati; Gunawan Gunawan (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The productivity of palm oil plantations are generally still low compared to the potential productivity of the land. Fertilization is an important factor in acheving high productivity, mainly to meet the requirement of nutrient avaibility. The research objective was to determine the avaibility of nutrient in oil palm leaves from the application of organic matter in modified biopore infiltration pit. This research was conducted in palm oil plantation PTPN 13 Pelaihari Tanah Laut,in 2013 and 2014. Sample collection were done by taking a leaf on the 17th oil palm midrib, which was taken using a purposively sampling spread system. The results showed a low level of nutrient content of nitrogen, potassium, and magnisium in plant leaf tissue in the palm oil plantation. Content of Phosfat in optimum level, and Calcium elements found in a state of excess.